The Problem of Soul Today. - Siemianowski, Antoni (Filozofia Chrześcijańska, 2010)
The article is a short introduction into a discussion on soul. Not only in psychology, but in the so called empirical sciences the topic of soul is absent or omitted with embarrassment as a metaphysical problem. It is the result of a long process of materialistic and anti-metaphysical tendencies increasing in the European culture. The question about soul includes relevant questions concerning man. Thus we should pose them and search for answers anew in the context of essential questions on man, his nature and the sense of existence.